1994
DOI: 10.4098/at.arch.94-19
|View full text |Cite
|
Sign up to set email alerts
|

Home range size and its development for fallow deer in the Blue Mountains, New Zealand

Abstract: G. 1994. Home range size and its development for fallow deer in the Blue Mountains, New Zealand. Acta theriol. 39: 159-175.Fifty-nine fallow deer Dama dama dama (Linnaeus, 1758) fitted with radio collars were monitored in the Blue Mountains, Otago, New Zealand, between September 1985 and February 1988 to determine home range size and patterns of range development. Fallow deer occupy small annual ranges, averaging 66 ha for females and 189 ha for males (90% isopleths calculated by the Harmonic Mean method). F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 10 publications
3
18
0
Order By: Relevance
“…Seasonal analysis revealed small home range outside the rutting period comparable to those reported by Nugent (1994) in the Blue Mountains (New Zealand). Interestingly thirteen female fallow deer monitored at the same time of the present study showed, in spite of a smaller body size, larger annual and seasonal home ranges than males outside the rutting period (Ciuti et al 2003).…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Seasonal analysis revealed small home range outside the rutting period comparable to those reported by Nugent (1994) in the Blue Mountains (New Zealand). Interestingly thirteen female fallow deer monitored at the same time of the present study showed, in spite of a smaller body size, larger annual and seasonal home ranges than males outside the rutting period (Ciuti et al 2003).…”
Section: Discussionsupporting
confidence: 51%
“…Nugent (1994) reported a mean annual home range, calculated by the 100% MCP method, of 309.5 ha for the male fallow deer of the Blue Mountains in New Zealand. Home range for male fallow deer in the New Forest, southern England, calculated over May-September, varied in size from 55 to 260 ha (MCP 100%), with a mean value of 107 ha (Rand in Putman 1986).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In mixed forest in the Blue Mountains, annual home range sizes for female fallow varied from 0.3 km 2 to 5.3 km 2 , mostly <1.0km 2 (Nugent 1994). Annual range size of resident females averaged 0.8 km 2 , and few shifted during the year (5%); subadults had larger ranges than fawns or adults.…”
Section: Social Organisation and Behaviourmentioning
confidence: 99%
“…Home range studies for fallow deer, as well as insular populations of white-tailed deer in the southeastern United States are lacking. However, home range size constructed using MCPs for both male and female LSSI fallow deer are larger than MCPs reported for fallow deer in Italy (Davini et al 2004), New Zealand (Nugent 1994), as well as estimated home range size from the New Forest of England (Rand in Putnam 1986).…”
Section: Discussionmentioning
confidence: 91%